Effects of a group-based weight management programme on anxiety and depression: a randomised controlled trial (RCT) - Heath, L; Jebb, S; Stevens, R; Wheeler, G; Ahern, A; Boyland, E; Halford, J; Aveyard, P (Public Library of Science, 2022)
Objectives The aim was to investigate the impact of a group-based weight management programme on symptoms of depression and anxiety compared with self-help in a randomised controlled trial (RCT). Method People with overweight (Body Mass Index [BMI]≥28kg/m2) were randomly allocated self-help (n = 211) or a group-based weight management programme for 12 weeks (n = 528) or 52 weeks (n = 528) between 18/10/2012 and 10/02/2014. Symptoms were assessed using the Hospital Anxiety and Depression Scale, at baseline, 3, 12 and 24 months. Linear regression modelling examined changes in Hospital Anxiety and Depression Scale between trial arms. Results At 3 months, there was a -0.6 point difference (95% confidence interval [CI], -1.1, -0.1) in depression score and -0.1 difference (95% CI, -0.7, 0.4) in anxiety score between group-based weight management programme and self-help. At subsequent time points there was no consistent evidence of a difference in depression or anxiety scores between trial arms. There was no evidence that depression or anxiety worsened at any time point. Conclusions There was no evidence of harm to depression or anxiety symptoms as a result of attending a group-based weight loss programme. There was a transient reduction in symptoms of depression, but not anxiety, compared to self-help. This effect equates to less than 1 point out of 21 on the Hospital Anxiety and Depression Scale and is not clinically significant.